2006
DOI: 10.1371/journal.pgen.0020131
|View full text |Cite
|
Sign up to set email alerts
|

Novel STAT1 Alleles in Otherwise Healthy Patients with Mycobacterial Disease

Abstract: The transcription factor signal transducer and activator of transcription-1 (STAT1) plays a key role in immunity against mycobacterial and viral infections. Here, we characterize three human STAT1 germline alleles from otherwise healthy patients with mycobacterial disease. The previously reported L706S, like the novel Q463H and E320Q alleles, are intrinsically deleterious for both interferon gamma (IFNG)–induced gamma-activating factor–mediated immunity and interferon alpha (IFNA)–induced interferon-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
185
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(192 citation statements)
references
References 55 publications
4
185
0
3
Order By: Relevance
“…Gene targeting studies confirmed the pivotal role that Stat1 plays in the biological response to both type I and type II IFNs (20,21). Consistent with this, humans expressing Stat1 mutants exhibit increased susceptibility to viral and bacterial infections (22). Intriguingly, Stat1 target genes appear to promote inflammation and antagonize proliferation.…”
Section: The Statsmentioning
confidence: 57%
“…Gene targeting studies confirmed the pivotal role that Stat1 plays in the biological response to both type I and type II IFNs (20,21). Consistent with this, humans expressing Stat1 mutants exhibit increased susceptibility to viral and bacterial infections (22). Intriguingly, Stat1 target genes appear to promote inflammation and antagonize proliferation.…”
Section: The Statsmentioning
confidence: 57%
“…[14][15][16][17] Six mutations, E320Q, Q463H, K637E, M654K, K673R and L706S in STAT1, have been reported ( Figure 1A). [14][15][16][17] The L706S mutation affects the tail segment domain of STAT1, abolishing phosphorylation at Y701. 14 The E320Q and Q463H mutations affect the DNA-binding domain.…”
Section: Introductionmentioning
confidence: 99%
“…14 The E320Q and Q463H mutations affect the DNA-binding domain. 15 They have no effect on STAT1 phosphorylation, but modify the DNA-binding capacity of GAF, impairing January 6, 2013. Manuscript accepted on April 5, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…1A). However, the critical residues for DNA binding and phosphorylation have been identified as Gln-463 and Tyr-701, respectively (5,6). In contrast, GOF mutations clearly accumulate in the CCD and the DBD (Fig.…”
mentioning
confidence: 98%
“…1A). The loss-of-function (LOF) 2 mutations have been associated with the pathogenesis of Mendelian susceptibility to mycobacterial disease, which is a rare syndrome characterized by infections with weakly virulent mycobacteria (5,6). On the other hand, its gain-of-function (GOF) mutations exhibit different immunological defects.…”
mentioning
confidence: 99%